2018
DOI: 10.26444/aaem/92650
|View full text |Cite
|
Sign up to set email alerts
|

Afamin and adropin in patients with alcohol-induced liver cirrhosis

Abstract: The aim of the study was to determine serum concentrations of afamin and adropin in patients with alcoholic liver cirrhosis and to define their correlation with the stage of disease. The study included 99 patients with alcoholic cirrhosis from the region of Lublin, (Eastern Poland). Liver cirrhosis was diagnosed based on clinical features, history of heavy alcohol consumption, laboratory tests and abdominal ultrasonography. The control group consisted of 20 healthy individuals without liver disease who did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Related results were reported by Chen in mice [10]. On the other hand, other studies showed an increase in serum adropin levels in liver cirrhotic and hepatitis patients [11,12].…”
Section: Introductionsupporting
confidence: 78%
“…Related results were reported by Chen in mice [10]. On the other hand, other studies showed an increase in serum adropin levels in liver cirrhotic and hepatitis patients [11,12].…”
Section: Introductionsupporting
confidence: 78%
“…While some have been implicated in liver disease confirming previously published findings, such as C7 (ref. 50 ), LGALS3BP 51 , TGFBI 52 , ALDOB 21 , AFM 21 , 53 , TTR 54 , QSOX1 (ref. 52 ), F2 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…These levels were further reduced in NAFLD patients with insulin resistance 10 . In a study of 99 patients with alcoholic cirrhosis, increased adropin levels were associated with increased severity of the liver dysfunction as assessed by the Child–Pugh score 17 …”
Section: The Role Of Adropin In Regulation Of Metabolic Pathways and mentioning
confidence: 98%
“…10 In a study of 99 patients with alcoholic cirrhosis, increased adropin levels were associated with increased severity of the liver dysfunction as assessed by the Child-Pugh score. 17 Enho gene expression in the liver is regulated by nutrition. In fed conditions, adropin levels are regulated by dietary macronutrients and increase with dietary fat content.…”
Section: The Role Of Adropin In Regulation Of Metabolic Pathways Anmentioning
confidence: 99%